REFLECTION OF THE MORAL THOUGHTS OF SOCIETY IN ART (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The article examines the reflection of moral ideas in art. Art was considered as one of the means of forming the moral qualities of a person, high feelings and moral convictions. The main mission of art is to humanize a person and improve him morally. In fact, even in these types of art, in some cases, one can find a connection with morality, because all works of art play a humanizing role.
Keywords: art, morality, society, education, humanism, beauty, aesthetics, memory, value, image, emotion.